2019
DOI: 10.3390/jcm8091447
|View full text |Cite
|
Sign up to set email alerts
|

Mucins as a New Frontier in Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most common idiopathic interstitial pulmonary disease with a median survival of 3–5 years after diagnosis. Recent evidence identifies mucins as key effectors in cell growth and tissue remodeling processes compatible with the processes observed in IPF. Mucins are classified in two groups depending on whether they are secreted (secreted mucins) or tethered to cell membranes (transmembrane mucins). Secreted mucins (MUC2, MUC5AC, MUC5B, MUC6-8 and MUC19) are released to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 185 publications
(239 reference statements)
0
38
1
Order By: Relevance
“…5 MUC1 has been studied in many diseases, such as tumor, respiratory diseases, and inflammatory bowel disease, and its vital role in the pathogenesis of these diseases has been demonstrated. 6,8 However, there is no report on the role of MUC1 in NEC so far. Our study showed that the expression of MUC1 was dramatically decreased in the intestinal tissue of NEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 MUC1 has been studied in many diseases, such as tumor, respiratory diseases, and inflammatory bowel disease, and its vital role in the pathogenesis of these diseases has been demonstrated. 6,8 However, there is no report on the role of MUC1 in NEC so far. Our study showed that the expression of MUC1 was dramatically decreased in the intestinal tissue of NEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gel‐forming mucin glycoproteins form the major components of mucus and are the main products of goblet cells. Mucins are divided into two subtypes: cell surface‐tethered/membrane‐bound mucins (MUC1, MUC3A/B, MUC4, MUC12‐17 and MUC20‐22) and secreted mucins 21 . Secreted mucins are further divided into two subfamilies, gel‐forming (MUC2, MUC5AC, MUC5B, MUC6 and MUC19) and non–gel‐forming (MUC7‐9) mucins, which maintain the structure and organization of the mucous gel and control its viscoelastic properties 21 .…”
Section: The Mucous Barriermentioning
confidence: 99%
“…Mucins are divided into two subtypes: cell surface‐tethered/membrane‐bound mucins (MUC1, MUC3A/B, MUC4, MUC12‐17 and MUC20‐22) and secreted mucins 21 . Secreted mucins are further divided into two subfamilies, gel‐forming (MUC2, MUC5AC, MUC5B, MUC6 and MUC19) and non–gel‐forming (MUC7‐9) mucins, which maintain the structure and organization of the mucous gel and control its viscoelastic properties 21 . Cell‐tethered mucins form a gel‐like layer around cilia of the respiratory epithelium that aid normal ciliary action of moving mucus in mucociliary clearance mechanisms 4 .…”
Section: The Mucous Barriermentioning
confidence: 99%
“…We also observed that 7118 TGAKIKLVGT 7127 derived from MUC19 reduced the levels of TNF-α, IL-1β and IL-6 in H 2 O 2 -treated A549 cells and the degree of decrease is related to the concentration of peptide as shown in Figure 5. As a secreted mucin MUC19, is released to the extracellular medium and has been identi ed in respiratory, digestive, and reproductive tracts [73]. It has been reported that MUC19 was differentially regulated after exposure to in ammatory cytokines [74].…”
Section: Discussionmentioning
confidence: 99%